Perspectives for Developing the Jurisdictions and Procedures of the Jordanian Administrative Judiciary: A Critical & Comparative Study - Abuirmilah, Bassam; Al Zubaidi , Khalid; El-Manaseer, Suhaib Ahmad (Journal of Ecohumanism, 2024)
Objective: This study's objective is to reorganise the rules of jurisdiction of the Jordanian administrative judiciary and the procedures related to it by following the critical and analytical approach to the provisions of the effective Jordanian Administrative Judiciary Law No. 27 of 2014. Method: This research is based on collecting information from two primary sources. The first source is the collection of information and observations of Jordanian Jurists and others related to the (JAJL), which came in the form of criticisms directed at this law through websites. The second source of information gathering – which is no less important than the first – is the amended Law of the Egyptian Council of State No. 47 of 1972, through which we were able to believe in the basic points that must be amended in the (JAJL) in question to ensure the achievement of the public interest and the protection of individual rights. Results and conclusion: The study reached some conclusions and suggested recommendations, the most important of which is: The fact that achieving the advantage of litigation on two levels in the Jordanian Administrative Judiciary Law does not achieve social justice and protect the rights of individuals as it should unless it requires the specialisation of judges in the administrative field.